Chemical Conditions of SiCNO Film Exposed to ClF3 Gas. (4th October 2021) - Hori, Kenta; Kawakami, Hiroki; Habuka, Hitoshi
Abstract : A SiCNO film containing 28% nitrogen was formed by plasma-enhanced chemical vapor deposition with no heating assistance using SiH3 CH3, N2 and Ar gases. The 15 nm thick layer of the film was then etched off utilizing 10% ClF3 gas at room temperature for 1 min. After etching, the fluorine and chlorine concentrations within the film did not increase but they became higher at the surface. The removal rate of Si–N component was considered to be faster than that of Si–C, Si–O and C–N components, based on the X-ray photoelectron spectroscopy results. Overall, the etching was considered to occur following the etching behavior of the components formed between four elements, that is, Si, C, N, and O.